Overview of Food Management in the Nutrition Installation of Madina General Hospital Bukittinggi in 2024 - Utami, Patrianisa; Adzkia, Legabina; Susanti, Elsi (CV. Dyoqu Publishing Management, 2025)
Background: Hospital nutrition installations play an important role in ensuring the safety and quality of patient food through the application of sanitation and hygiene principles. Non-standardized food management can pose serious health risks, especially in a hospital setting. Aims: This study aims to describe food management in the Nutrition Installation of Madina General Hospital Bukittinggi, including aspects of material selection, storage, processing, transportation, and food presentation. Methods: This study used a descriptive method with a qualitative approach. Data were collected through direct observation and semi-structured interviews with three main informants and triangulation with the head of the nutrition sub-unit. Data analysis techniques followed the stages of data reduction, data presentation, and conclusion drawing according to Miles and Huberman. Result: The results show that the selection of food ingredients is done carefully and according to standards. Storage meets FIFO and FEFO principles with separation of dry and wet warehouses. Food processing follows a 10-day menu cycle and is tailored to the patient's diet, although the main kitchen space is still not physically ideal. Food transportation is done on time using closed containers, and serving is done according to dietary standards and patient portions. Conclusion: In general, the Madina General Hospital Nutrition Installation has carried out food management according to food sanitation principles, although improvement is still needed in the aspects of kitchen facilities and supervision of the use of PPE by officers